2014
DOI: 10.1136/lupus-2014-000038
|View full text |Cite
|
Sign up to set email alerts
|

Blood-based candidate biomarkers of the presence of neuropsychiatric systemic lupus erythematosus in children

Abstract: ObjectiveTo examine select brain-reactive proteins for their usefulness to serve as blood-based biomarkers in the screening for neurocognitive deficits in childhood-onset systemic lupus erythematosus (cSLE-NCD).MethodsPatients withcSLE (n=40) were studied longitudinally (month 1; month 18): working memory, psychomotor speed and visuoconstructional ability were assessed using formal neurocognitive testing to determine the presence of cSLE-NCD. Patients also completed the computerised Paediatric Automated Neurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Anti–ribosomal P antibodies have been linked to psychosis and depression and might be involved in cognitive decline in cSLE . Other brain‐reactive antibodies are likely involved in the development of NPSLE, possibly contributing to the diverse clinical and imaging features of NPSLE.…”
Section: Introductionmentioning
confidence: 99%
“…Anti–ribosomal P antibodies have been linked to psychosis and depression and might be involved in cognitive decline in cSLE . Other brain‐reactive antibodies are likely involved in the development of NPSLE, possibly contributing to the diverse clinical and imaging features of NPSLE.…”
Section: Introductionmentioning
confidence: 99%
“…As of April 2015, eight human studies with specific analyses performed for associations between a priori defined cognitive dysfunction as a NPSLE manifestation and serum anti-NR2A/B antibodies were published [ 9 , 19 , 31 , 43 , 44 , 45 , 46 , 47 ]. Table 1 summarizes the characteristics and findings of the studies.…”
Section: Mechanisms Of Cognitive Dysfunctionmentioning
confidence: 99%
“…All eight studies synthesized DWEYSVWLSN or DWEYS peptides for ELISA testing and reported presence of anti-NR2A/B antibodies in comparison to the optical density values of the controls, each using slightly different definitions and cut-offs [ 9 , 19 , 31 , 43 , 44 , 45 , 46 , 47 ]. Six of the studies were cross-sectional and two studies were longitudinal [ 9 , 19 , 31 , 43 , 44 , 45 , 46 , 47 ]. Between 14% and 35% of the SLE patients were anti-NR2A/B antibody positive [ 9 , 19 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Mechanisms Of Cognitive Dysfunctionmentioning
confidence: 99%
See 2 more Smart Citations